2023
DOI: 10.3390/antibiotics12050925
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors Associated with Risk of Death or Admission to Intensive Care Unit in Internal Medicine Patients with Sepsis: A Comparison of Statistical Models and Machine Learning Algorithms

Abstract: Background: Sepsis is a time-dependent disease: the early recognition of patients at risk for poor outcome is mandatory. Aim: To identify prognostic predictors of the risk of death or admission to intensive care units in a consecutive sample of septic patients, comparing different statistical models and machine learning algorithms. Methods: Retrospective study including 148 patients discharged from an Italian internal medicine unit with a diagnosis of sepsis/septic shock and microbiological identification. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Having shown that MR-proADM correlated with organ damage, we also tested its correlation with prognosis, which was significant. This reinforces data already described in the literature [6,7,[17][18][19][20][21][22][23]49,[54][55][56][57][58][59][60][61][62].…”
Section: Mr-proadm Levels and Organ Damage And Outcomesupporting
confidence: 91%
“…Having shown that MR-proADM correlated with organ damage, we also tested its correlation with prognosis, which was significant. This reinforces data already described in the literature [6,7,[17][18][19][20][21][22][23]49,[54][55][56][57][58][59][60][61][62].…”
Section: Mr-proadm Levels and Organ Damage And Outcomesupporting
confidence: 91%
“…Moreover, it has been witnessed that there is virtually no benefit of using more complex machine learning methods over logistic regression ( 37 ). In particular, logistic regression has shown good calibration compared to other approaches ( 38 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…Furthermore, MR-proADM acts as a biomarker for sepsis, reflecting the degree of oxidative stress and indicating the severity of the condition in line with organ damage and prognosis [ 120 , 124 ]. From a clinical perspective, MR-pro-ADM can accurately detect patients with one or multiple organ failures, particularly showing a stronger correlation for certain variables such as acute kidney injury (AKI), GCS < 15, and the requirement for intensive care unit (ICU) transfer indicating a more severe prognosis [ 19 , 20 , 120 , 125 , 126 , 127 , 128 , 129 ].…”
Section: Pathophysiology Of Endothelitis: Adrenomedullin Expressionmentioning
confidence: 99%